Postgraduate studies in Visual Arts and teacher training in southern Brazil (Palíndromo, 2022)
In this research, the object of study on which it is based is the training of teachers, in the context of Postgraduate Programs in Visual Arts of public institutions in southern Brazil, which offer the Doctorate and/or Master’s Degree. Data were collected, together with the programs, in order to understand how the production of theses and dissertations reveal the problems experienced in graduate studies in Visual Arts from the perspective of teacher training. To substantiate this reflection, 430 surveys were collected, in the period between 2014 and 2019, in the PPGAV of UFRGS, PPGAV of UDESC, PPGArt of UFSM, and PPGAVI of UFPEL. Among other things, theses and dissertations reveal the need to study teacher training in Brazil due to: lack of research on this subject in postgraduate studies; the constant attacks on the Visual Arts area and the recurrent threat of removal of the Arts subject from the school curriculum; to establish an opinion in face of a rushed formation; act against precariousness and avoid the dismantling of education. As theoretical, methodological, and pedagogical support, a reference is made to the Historical-Dialectical Materialism developed by Karl Marx (1978; 1985; 1998) and the Historical-Critical Pedagogy conceived by Dermeval Saviani (1984; 2009; 2013; 2018; 2019). It reinforces the need to carry out concrete actions that make educational praxis in the visual arts viable and actions that broaden the debate on teacher education. Because, in Brazil, people do not act only as researchers, they act together in teaching in universities, in schools, as well as in informal teaching in cultural spaces.
Keywords: Teacher Training; Postgraduate Studies; Visual Arts; Observation; Historical-Critical Pedagogy